Molecular Adaptation of Cardiac Remodeling in Metabolic Syndrome: Focus on AMPK, SIRT1 and PGC-1a - Ramadhan, Andika Yusuf; Soetikno, Vivian (Cell and BioPharmaceutical Institute, 2024)
Obesity, lack of physical activity, and genetic predisposition might play a pivotal role in pathogenesis of metabolic syndrome. Cardiac function alteration including hemodynamic changes, contractility function, arrhythmia, and cellular respiratory function, might happen due to chronic condition in metabolic syndrome. Insulin resistance, neurohormonal activation and chronic inflammation might contribute to these changes. Cardiomyocyte had capabilities to adapt from these abnormalities, one of them is the activation of cellular pathway to resist cardiac injury from metabolic syndrome. This molecular pathway involves three proteins, including AMP-activated protein kinase (AMPK), sirtuin-1 (SIRT1) and peroxisome proliferator-activated receptor γ coactivator-α (PGC-1α). The aim of this narrative review is to elucidate role of AMPK, SIRT1, and PGC-1α in cardiac adaptation against cardiac dysfunction in metabolic syndrome. AMPK, SIRT-1, and PGC-1α contribute to adapt and to repair the cardiac injury resulting from celullar and mechanical stress from metabolic syndrome and prevent cardiac remodeling event. Several pathological events, such as insulin resistance, induce alteration of switching energy fuel to the heart, causing cardiomyocte to rely on glucose metabolism and lipotoxicity, leading to damages of cardiomyocyte through reactive oxygen species (ROS) generation and lipid peroxidation. Increase of ROS promotes cardiac injury followed by necrotic and apoptotic events. AMPK, SIRT1, and PGC-1α act as cardioprotector molecule against metabolic syndrome insults to several mechanism such as: AMPK play role as counter act of lipotoxicity and insulin resistance through increasing insulin sensitivity and regulate redox reaction. SIRT1 plays role in regulating apoptotic genes and PGC-1α repairs cardiac fuel sources. Activation of AMPK/SIRT1/PGC-1α prevent cardiac remodeling due to metabolic syndrome by increasing insulin sensitivity, increases mitochondrial biogenesis and reduce pro-apoptotic signals in cardiomyocte.Keywords: AMPK/SIRT1/PGC-α, cardiac remodeling, metabolic syndrome